Selectivity switch in the synthesis of vinylgold(I) intermediates - Hashmi, A. Stephen K.; Schuster, Andreas M.; Gaillard, Sylvain; Cavallo, Luigi; Poater, Albert; Nolan, Steven P. (Organometallics, 2011)
An unexpected regioselectivity reversal was observed in the synthesis of vinylgold(I) complexes from propargyl carboxamides. The use of [Au(IPr)(OH)] affords preferentially vinylgold(I) complexes resulting from a 5-exo-dig cyclization, whereas the use [Au(IPr)]+ species, generated in situ starting from [Au(IPr)(Cl)] and AgOTf, leads to vinylgold(I) complexes which form via a 6-endo-dig cyclization, This unexpected “selectivity switch” for this cyclization led us to propose two different reaction pathways enabling the formation of the two different products. One mechanism involves the [Au(IPr)]+ species with “classical” π activation of the alkyne framework of the carboxamides, and the second represents an “unusual” use of the basic Brønsted character of [Au(IPr)(OH)]. Mechanistic and DFT studies support the mechanistic hypotheses.